Analysis of Local Fashion Competition Readiness through Consumer Shopping Intention: A Media and Brand Authenticity Approach - Edy Yulianto Putra; Warna Gamelia; Hepy Hefri Ariyanto (Jurnal Manajemen dan Kewirausahaan, 2024)
The fashion industry in Indonesia faces competitive challenges as digital technology develops. The emergence of new local fashion brands and consumers' easy access to global brands through digital platforms have created intense competition. To compete effectively, a deep understanding of shopping intentions is crucial for local fashion brands. Therefore, this study was designed to determine the variables influencing local fashion purchase intention, specifically focusing on advertising, entertainment, e-WOM, interaction, and trendiness, while also examining the mediating roles of brand trust and brand engagement on digital media. The analysis was conducted using SmartPLS 3 and SPSS, analyzing data from 350 respondents who are local fashion users in the Riau Islands Province. The results indicate that e-WOM, interaction, trendiness, brand trust, and brand engagement positively and significantly influence the purchase intention of local fashion users. Notably, e-WOM emerged as a strong driver of brand trust, enhancing the likelihood of consumers engaging with and purchasing from local brands. Furthermore, interaction with brands and perceived trendiness played critical roles in shaping consumer perceptions and fostering loyalty. This research is expected to provide valuable insights for local brands, enabling them to refine their marketing strategies in this highly competitive digital era. By leveraging the identified factors, local fashion brands can enhance their appeal, build stronger relationships with consumers, and ultimately improve their market positioning against global competitors. The findings underscore the importance of adapting to digital trends and consumer preferences to thrive in the evolving fashion landscape